Tree and shrub species integration in the crop-livestock farming system - Sisay, M.; Mekonnen, Kindu (African Journals Online, 2013)
Tree and shrub integration has been promoted as a means of enhancing rural livelihoods through sustaining watershed provision of services and products, especially in Ethiopia. However, research to support this effort has been limited. This study was conducted in Borodo watershed in central Ethiopia, to identify constraints to the process of tree and shrub integration in the watersheds. A household survey was conducted, supplemented with focus group discussions (FGDs), key informant interview and field observations. A total of 31tree and 11 shrub species were identified in different niches in the watershed. The key constraints to tree and shrub species integration included shortage of arable land, soil cracking, free grazing, lack of seedlings of desired species and water-logging. The main catalysts to the integration were availability of information on improved integration and cash for investment in the required activities, easy land certification and market opportunity for tree and shrub products. The tree and shrub growing niches preferred by farmers were homesteads (95.5%), gully sides (67.4%), stream sides (61.8%) road sides (60.7%), and crop land (12.4%). It is essential to address the factors that hinder tree and shrub species integration at various growing niche so as to improve the availability of tree products and services. Moreover, the capacity of farmers should be upgraded through training and demonstration of best tree planting, management and utilisation practices.